Global Research Trends on 21st Century Teacher Competency Using Bibliometric Analysis - Chotijah, Hindun Yafa; Suparman, S; Kusumaningtyas, Dian Arta; Raman, Arumugam (CV Sinergi Ilmu dan Publikasi, 2025)
Educators are critical facilitators of learning and development in the education system. This study investigates 21st-century teacher competencies in education between 2015 and 2024, analysing publication trends, citation patterns, and their alignment with the Sustainable Development Goals (SDGs). This study uses bibliometric analysis and systematic literature review methodologies, leveraging data from Dimensions.ai (January 15, 2025) via the PRISMA framework, which yielded 985 data points. Analysis through VOS viewer maps collaboration networks and assesses citation impacts, revealing a consistent rise in publications and citations over the period. Notably, the most cited works appeared in reputable, indexed journals. The bibliometric map identifies eight distinct clusters, with “21st-century skills” as the central theme. Current trends link teacher competencies to key areas such as Digital Competency, TPACK (Technological Pedagogical Content Knowledge), Pre-service Teacher preparation, Communication Skills, and Pedagogical Competence. Findings highlight a strong connection between 21st-century competencies and SDG 4 (Quality Education), underscoring their role in improving global education quality. The study emphasizes the necessity of equipping teachers with these competencies to address modern educational challenges effectively. The novelty of this study lies in its integrative approach to bibliometric and systematic review methods to comprehensively map global research trends and gaps in 21st-century teacher competencies over the past decade.